Acupuncture decreases amygdala functional connectivity in subjective tinnitus - Zhang, Yating; Zha, Bixiang; Shi, Haiping; Cheng, Ling; Fan, Yinqiu; Zhang, Wanlin; Rong, Zhihao; Jin, Zhaoxing; Gao, Nan; Yang, Jun; Zhang, Qingping (Frontiers in Neurology, 2022)
Introduction Subjective tinnitus is a common and intractable ear disease. The effectiveness of acupuncture in the treatment of subjective tinnitus has been confirmed, but its mechanism of action is not clear. The structures of the amygdala (AMYG) are mainly closely related to emotion in the human brain. This study aimed to investigate the changes in functional connectivity (FC) of AMYG in subjective tinnitus to elucidate the neural mechanism of acupuncture. Methods Correlation scale scores of 26 patients with subjective tinnitus were collected, including Tinnitus Evaluation Questionnaire (TEQ), Tinnitus Handicap Inventory (THI) and Visual Analog Scale (VAS). Meanwhile, rs-fMRI data were collected before and after acupuncture treatment in the patients, and in healthy controls (HC) matching the patient's gender and age. Then, AMYG was selected as region of interest to perform FC analysis. Finally, FC patterns of AMYG were first compared between patients with subjective tinnitus and HC, and then within subjects pre-acupuncture and post-acupuncture. Simple linear regression models between correlation scale scores and FC-values were established as well. Results Acupuncture treatment relieved the severity of tinnitus. With the acupuncture treatment, the total THI score, TEQ score, and VSA score of patients were significantly lower than before (p < 0.05). Compared with HC, FC of tinnitus patients between AMYG and right inferior temporal gyrus and right precuneus significantly decreased before acupuncture (voxel p < 0.001, cluster p < 0.05, corrected with GRF), while FC of tinnitus patients between AMYG and left superior frontal gyrus and right superior temporal gyrus significantly decreased after acupuncture treatment (voxel p < 0.001, cluster p < 0.05, corrected with GRF). FC of tinnitus patients between the AMYG and right superior frontal gyrus and left paracingulate gyrus showed significant decrease after acupuncture treatment (voxel p < 0.001, cluster p < 0.05, corrected with GRF). Besides, the linear regression models of the effect of THI on FC and VAS on FC performed were statistically significant (p < 0.05). Discussion The findings demonstrate that acupuncture can decrease FC of AMYG, which could be positively correlated with the relief of tinnitus symptoms. This result suggests that acupuncture stimulation can effectively relieve the severity of tinnitus by decreasing FC of AMYG in subjective tinnitus patients.